The Implementation of Humanist Education-Based Classroom Management in Madrasah Ibtidaiyah Muhammadiyah Semanu - Hendro Widodo; Afnan Subekti; Mohammad Jailani (Badan Litbang dan Diklat Kementerian Agama RI, 2025)
This study examines classroom management based on humanist education at Madrasah Ibtidaiyah Muhammadiyah Semanu (MIM Semanu). The study aims to describe the implementation of classroom management and identify the factors that support and hinder it. A descriptive qualitative research method was employed, involving the principal, homeroom teachers for grades 1-4, and students as subjects. Data collection techniques included interviews, observations, and documentation, with data validity ensured through triangulation of sources and techniques. Data analysis followed Miles and Huberman's framework, encompassing data collection, reduction, presentation, and conclusion drawing. The results of this study indicate that MIM Semanu has implemented humanist classroom management practices, including strategic seating arrangements, educational classroom decorations, adequate ventilation and lighting, and structured class management. Guidance is provided in a friendly and fair manner, and student grouping is attractively organized according to class conditions. Supporting factors include adequate facilities and infrastructure, enthusiastic students, and innovative educators. Conversely, inhibiting factors comprise some students' difficulties in receiving material, lack of awareness of obligations, and the diversity of students, which complicates the provision of personalized attention.